Seni Islam sebagai Media Dakwah (Studi Kasus: Kesenian Tari Badui di Dusun Semampir, Desa Tambakrejo, Kecamatan Tempel, Kabupaten Sleman, Yogyakarta) - Nur Aminah Nasution (JUSPI (Jurnal Sejarah Peradaban Islam), 2017)
This research examines about Islamic art (the art of dancing the Bedouin Village of Semampir) as a media of religious proselytizing. This theme is considered to be important, considering one of the efferts in delivering media of religious proselytizing of Islam is through art. As always practiced by Wali Songo in Java, with the use of various arts for this media of religious proselytizing of Islam. This study is besed of field research against Bedouin dance arts in the Village of Semampir. The primary source is the result of interviews with people involved with this study and other writings that are relevant. Results of the study show that this simple Bedouin dance art is really a media propaganda for the community of the Village of Semampir in particular and society in General. Factually, this art has renewed the knowledge society, which was not previously so religious practices in response to the group, as well as add to the scientific vocabulary for readers in General and especially writers. Side of Islam is in the art of dances at the Bedouin poetries while performing. The poetries are divided into two languages, namely Arabic and Indonesian, Arabic poetry taken from the book of Arabic Verse Barzanji and Indonesian poetry contains the opening and closing greetings. As for the movements of the dencer describes a group of people practicing war, as it has always been practiced by Bedouin Arabs.Keywords: Islamic Art, Art Dance Bedouin Village of Semampir, Media of Religious Proselytizing.